Meinong and Husserl on Existence. Two Solutions of the Paradox of Non-Existence - Giuliano Bacigalupo (Philosophia Scientiæ, 2014)
This paper analyzes and compares the attempts at solving the paradox of non-existence put forward by Alexius Meinong and Edmund Husserl. It will be argued that Meinong's solution is not convincing since he retreats from the field of predicate logic, in which the paradox arises, to a version of propositional logic. On the other hand, Husserl's approach is more promising since he moves forward to an extension of predicate logic, where existential judgments have to be interpreted in relation to different contexts or, in Husserl's terminology, “spheres” or “levels of being”.